Tengmalm's owl Aegolius funereus found in bare karst area of Pag island (N Dalmatia, Croatia) - Denac, Damijan (Acrocephalus, 2005)
On 28 Apr 2005, a dead young (2Y) male Tengmalms Owl Aegolius funereus was found on the island of Pag (N Dalmatia, Croatia) in bare karst area of the rocky Ravna plateau (app. 200 m a.) of Mt. Dolac. So far, only four published data of Tengmalms Owl occurrence in the coastal part of Croatia exist, and all of them are older than 70 years. The bird most probably migrated to the island from its nearest breeding area-Mt. Velebit. According to the literature, part of the population, especially young birds and females,are nomadic during the non-breeding period. But the question on the habitat used on the island of Pag remains open. It is known that during the non-breeding period. But the question on the habitat used on the island of Pagremains open. It is known that during the non-breeding period, Tengmalms Owls usually move within their potential breeding range and habitat, which is probably not the case as far as this find is concerned. The carcass was found under the turbine of the wind farm, and collision with the turbine was clearlythe cause of the birds death. To our knowledge, no monitoring to evaluate the impact of the discussed wind farm on bird mortality exists, but should certainly be started in view of the references and data presented herewith.
Keywords: Birds; Ekosistem; bird; Ecosystem; Ptice; Croatia; Hrvaška; ornitologija; Pag; zoogeografija